An invisible patient: Healthcare professionals' perspectives on caring for adolescents and young adults who have a sibling with cancer. (20th November 2018) - Franklin, Marika; Patterson, Pandora; Allison, Kimberley R.; Rosso‐Buckton, Amanda; Walczak, Adam
Abstract: The impact of a young person's cancer diagnosis extends to siblings, yet support services to address siblings' needs are limited. This study explores healthcare professionals' (HCPs') perspectives on engaging and supporting adolescent and young adult (AYA, 12–25 years) siblings of young cancer patients in hospital settings. Semi‐structured interviews with nine HCPs explored participants' views on models of care, engagement and assessment of siblings, available services, barriers to care, and future directions. Participants understood the impact of cancer and need to support AYA siblings, but were unclear how these responsibilities fit in with existing models of care and clinical roles. Siblings' absence from hospitals complicated processes of engagement, assessment and provision of care, challenging some participants to engage siblings outside the clinical context. In the absence of direct contact, HCPs largely relied on patients and parents to report or refer siblings for care. Service and resource limitations further restricted the provision of support to siblings. Despite HCPs' recognition of the need to support siblings, their "invisibility, " lack of standardised assessment and service constraints complicate the provision of care in hospital settings. Integrating hospital‐based care with community services may better facilitate the engagement and support of AYA siblings.